Analisis Tarif Rumah Sakit Terhadap Kualitas Pelayanan Pasien Umum dan Pasien BPJS di Rumah Sakit Muhammadiyah Ahmad Dahlan Kota Kediri - Yohana Nilasari; Arisyahidin Arisyahidin; Eka Askafi (Otonomi, 2021)
The hospital of Muhammadiyah Ahmad Dahlan Kediri is a place that gives the service to individual’s health with hospitalized service, regular service and emergency service. The Hospital of Muhammadiyah Ahmad Dahlan Kediri is a hospital with class C that has capacity 205 beds. Bed Occupational Rate (BOR) for 4 years lately is around 52,5%. The operational expense of hospital is totally from the patients so that the position of customer is very important. This research Design Uses Correlational Analysis Survey Design by approaching Cross Sectional. It uses the population of all for long hospitalized patients that had got service in Hospital of Muhammadiyah Ahmad Dahlan Kediri, and their number is 125 patients with 55 patients as the sample, it is taken by using the technique of purposive sampling. The collection of Data uses the questioner. The data of Research was analyzed by Moderated Regression Analysis Test. there are 3 variables that become research material, from the 3 variables studied, there are a total of 23 question items. From each question item, both independent and dependent, it turned out to have a correlation probability value below 0.005 or the Service research variable data (X), General patient satisfaction (Y1) and BPJS patient satisfaction (Y2) at Muhammadiyah Ahmad Dahlan Hospital, Kediri City were declared valid. . From the results of the questionnaire obtained after being processed, it can be seen from the highest average value obtained in empathy from service providers, which is 3.69 which means the attitude of nurses and doctors is good when responding to questions from patients' families and hospital visitors. While the lowest average is 2.85, which is from the time of the doctor's examination according to the schedule. This explains that many patients are dissatisfied with the doctor's schedule for not being on time. There are two kinds of service rates at the Muhammadiyah Ahmad Dahlan Hospital, Kediri City, which results in differences in treatment for general patients and BPJS patients who seek treatment at Muhammadiyah Ahmad Dahlan Hospital, Kediri City. There is an effect of service rates on general patient satisfaction and BPJS patients at home. Muhammadiyah Hospital Ahmad Dahlan, Kediri City. Although there are differences in treatment and service, there are differences in satisfaction between general patients and BPJS patients at the Muhammadiah Ahmad Hospital. Dahlan, Kediri. Not too significant.